The Association Between Emotional Expression, Self Efficacy And The Recurrence Of Mental Disorder In Pagu Public Health Center, Kediri Regency - Agustin Widyowati; Suminah Suminah; Bhisma Murti; Aris Sudiyanto (Alma Ata University Press, 2020)
People with mental disorders experience an increase every year so that it becomes a global issue that requires attention in handling. The problem that often occurs in people with mental disorders is experiencing relapses. Patient recurrence can occur due to lack of family support, especially caregivers in providing care to sufferers. This study aimed to examine the association between emotional expression and self-efficacy with recurrence of mental disorders in Pagu Public Health Center, Kediri Regency, East Java. This was an analytic observational study with a crosssectional design. A sample of 38 families who had family members with mental disorders was selected for this study by multistage random sampling. The dependent variable was mental disorders recurrence. The independent variables were emotional expression and self-efficacy. The data were collected by questionnaire and analyzed by logistic regression. The recurrence of mental disorders increased with high emotional expression (OR= 12.25; CI 95%= 1.65 to 90.96; p= 0.14) and poor self efficacy (OR= 7.42; CI 95%= 5.08 to 51.06; p=0.042). The recurrence of mental disorders increases with high emotional expression and poor self efficacy, it is hoped that health workers can provide psychoeducation so that the caregiver can provide care to family members with mental disorders.